2011
DOI: 10.1007/s12011-011-9175-x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Regulates Gene Expression of Selenoprotein W in Chicken Gastrointestinal Tract

Abstract: Selenoprotein W (SelW) is an existing form of selenium (Se). Se influences the levels of SelW in mammals. However, little is known about the pattern of SelW expression in the gastrointestinal tract tissue of bird. The present paper describes the effects of different dietary levels of Se on the SelW mRNA expression in the gastrointestinal tract tissue of chicken. The expression levels of SelW mRNA and the Se contents in the gastrointestinal tract tissues (glandular stomach, gizzard, duodenum, small intestine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…There is evidence from in vitro and in vivo studies that expression of TrxR1, SelP, and SelW mRNA is highly up-regulated by SS supplementation in comparison with Se deficiency (Hill et al 1996;Hadley and Sunde 2001;Pagmantidis et al 2005;Gao et al 2012). However, the regulation of TrxR1, SelP, and SelW mRNA by different Se forms in avian liver, kidney, and muscle is not known.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence from in vitro and in vivo studies that expression of TrxR1, SelP, and SelW mRNA is highly up-regulated by SS supplementation in comparison with Se deficiency (Hill et al 1996;Hadley and Sunde 2001;Pagmantidis et al 2005;Gao et al 2012). However, the regulation of TrxR1, SelP, and SelW mRNA by different Se forms in avian liver, kidney, and muscle is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Se implements its biological function through incorporation into selenoproteins. In addition, Se deficiency caused injuries in several different chicken organs, including the brain (Sheng et al 2014;Xu et al 2013), muscles (Yao et al 2013a, b), the gastrointestinal tract (Gao et al 2012), the spleen (Yu et al 2011) and the liver (Sun et al 2011). The study of Fischer showed that the liver contains a high concentration of Se, which participates in many biological processes that range from cellular antioxidant defense to the protection and repair of DNA to apoptosis (Fischer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…SelW mRNA expression in the gastrointestinal tract, liver, pancreatic tissue; immune organs and skeletal muscle system in chickens are highly sensitive to Se supply (Li et al 2010;Gao et al 2011;Sun et al 2011;Wang et al 2011;Yu et al 2011;Ruan et al 2011). Pagmantidis et al (2005) reported that SelN and SelW expression levels in human intestinal Caco-2 cells is highly sensitive to Se-depletion and Seadequate conditions.…”
Section: Discussionmentioning
confidence: 99%